Six Sigma case studies with Minitab - Pochampally, Kishore K.; Gupta, Surendra M. (Boca Raton, Florida : CRC Press/Taylor & Francis Group, 2014)
'Six Sigma is one of the most widely used quality improvement methodologies today, both in manufacturing and service industries. Minitab{u0A73} a statistical software package that is often used in conjunction with Six Sigma projects. This book illustrates the application of Minitab{u09AF}r Six Sigma projects, using case studies in a variety of sectors, such as healthcare, manufacturing, airline, and fast food. Detailed steps and screenshots are provided to explain how to use a number of quality analysis and improvement tools in Minitab{uE806}igures will include Minitab{u0CE3}reenshots and Minitab{u0DEF}rksheets for the case studies will be available for download'--
Includes bibliographical references and index.
Keywords: Minitab; Six sigma (Quality control standard) -- Case studies; Quality control -- Data processing